Multiplicação in vitro e ex vitro de Ilex paraguariensis A. Saint Hilaire (erva-mate) - Quadros, Kenia Michele de (2013)
Holly (Ilex paraguariensis A. Saint Hilaire) plays an important economic, social and ecological throughout southern of Brazil; however, still requires efficient protocols for vegetative propagation of seedlings aiming planting of selected genotypes. This work aimed to study vegetative propagation technologies turned at mass production of holly seedlings through in vitro micropropagation, microcutting and minicutting. The propagation of explants derived from the apical and nodal holly segments from eight clones established in vitro was evaluated in four cultivations. It was also evaluated acclimatization and ex vitro rooting of microcuttings, testing different substrates, separated in two experiments. In experiment one, the substrates were used pure (carbonized rice husk, coarse sand, vermiculite, coconut fiber and commercial substrate of pine bark) and in the second experiment, the substrates were used in combination with equal proportions (carbonized rice husk and coarse sand; carbonized rice husk, coarse sand and commercial substrate of pine bark; carbonized rice husk and commercial substrate of pine bark). Holly minicuttings of two collections and four clones (CE1, CE2, EF6 and EF7) were treated with or without 3-indolibutírico acid (IBA) at a dose of 1.000 mg L-1 and then placed in a substrate composed by carbonized rice husk, coarse sand and commercial substrate of pine bark. Clones CE1 and CE2 coming from microcuttings ex vitro rooted and acclimatizated in the greenhouse, and the clones and EF6 EF7 come from cuttings rooted of epicormic shoots of two adult plants. From the second collection, it was followed the rooting evolution of four clones under evaluation at 15, 30, 45, 60 and 75 days. It is feasible the maintenance of holly germplasm bank, whereas complete plants derived from nodal segments and apical segments rooted in vitro, can be acclimated in a greenhouse for holly seedlings production, with the explants competence maintained over four cultivations. Holly microcuttings can be acclimated and ex vitro rooted, using as substrate the composition of the same proportions of carbonized rice husk and commercial substrate of pine bark or with carbonized rice husk, coarse sand and commercial substrate of pine bark. In holly minicutting, clones differ in rooting competence and induction period for root initiation, whereas the application of 3-indolibutiric acid does not affect the rooting of holly minicuttings. The closed system of cultivation in sand is feasible for conduct and management of holly ministumps aiming to collect the minicuttings. application of 3-indolibutiric acid does not affect the rooting of holly minicuttings. The closed system of cultivation in sand is feasible for conduct and management of holly ministumps aiming to collect the minicuttings.